2014
DOI: 10.1136/jclinpath-2013-202161
|View full text |Cite
|
Sign up to set email alerts
|

Axl receptor tyrosine kinase expression in breast cancer

Abstract: Aims Triple-negative breast cancer comprises a clinically aggressive group of invasive carcinomas. We examined a published gene expression screen of a panel of breast cancer cell lines to identify a potential triple-negative breast cancer-specific gene signature, and attempted to verify our findings by performing immunohistochemical analysis on tissue microarrays containing a large cohort of invasive breast carcinomas. Methods The microarray dataset for a panel of human breast cancer cell lines was interroga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 33 publications
(24 reference statements)
4
52
0
2
Order By: Relevance
“…S1) in 10 TNBC cell lines and found that AXL was significantly expressed in 7. These results are consistent with previous studies reporting that AXL is often upregulated in basal B and occasionally in basal A TNBC (20,21). Moreover, the cell lines in which AXL was most overexpressed (MDA-MB-231, BT549, HBL-100, BT20, and HS578T) are considered as highly invasive (22).…”
Section: Resultssupporting
confidence: 82%
“…S1) in 10 TNBC cell lines and found that AXL was significantly expressed in 7. These results are consistent with previous studies reporting that AXL is often upregulated in basal B and occasionally in basal A TNBC (20,21). Moreover, the cell lines in which AXL was most overexpressed (MDA-MB-231, BT549, HBL-100, BT20, and HS578T) are considered as highly invasive (22).…”
Section: Resultssupporting
confidence: 82%
“…S2). The observed percentage of AXL-positive TNBCs is consistent with recent previous reports (23,24).…”
Section: Axl Expression Correlates With a Mesenchymal Phenotypesupporting
confidence: 82%
“…3, 5a and 5b). Although vimentin expression has been found to consistently be associated with TNBC [14,13,12,11], one study found that Axl expression, while associated with aggressive disease, did not segregate with TNBC but was found across ER negative and ER positive subtypes [15]. Thus, vimentin may be a more selective marker for the basal B TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…While the basal A subtype retains a more epithelial phenotype, the basal B subtype possesses stem cell-like characteristics and also preferentially expresses specific markers, including the intermediate filament protein vimentin and receptor tyrosine kinase Axl [9]. Subsequent studies have explored using vimentin [11-14] or Axl [15] as TNBC/basal-like biomarkers in human breast tumors. Vimentin has been a particularly robust biomarker for TNBC, and vimentin and Axl have been associated with poor prognosis [11-15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation